Viral-Host Dependency Factors as Therapeutic Targets to Overcome Antiviral Drug-Resistance: A Focus on Innate Immune Modulation - Badia, Roger; Garcia-Vidal, Edurne; Ballana, Ester (Frontiers in Virology, 2022)
The development of antiviral drugs, has provided enormous achievements in our recent history in the fight against viral infections. To date, most of the approved antiviral drugs target virus-encoded proteins to achieve direct antiviral activity. Nonetheless, the inherent idiosyncrasy of viral mutations during their replication cycle, enable many viruses to adapt to the new barriers, becoming resistant to therapies, therefore, representing an ever-present menace and prompting the scientific community towards the development of novel therapeutic strategies. Taking advantage of the increasing knowledge of virus-host cell interactions, the targeting of cellular factors or pathways essential for virus survival turns into an alternative strategy to intervene in almost every step of viral replication cycle. Since host factors are evolutionary conserved, viral evasion to host-directed therapies (HDT) would impose a higher genetic barrier to the emergence of resistant strains. Thus, targeting host factors has long been considered an alternative strategy to overcome viral resistance. Nevertheless, targeting host factors or pathways potentially hints undesired off targets effects, and therefore, a critical risk-benefit evaluation is required. The present review discusses the current state-of-the-art on the identification of viral host dependency factors (HDF) and the workflow required for the development of HDT as antivirals. Then, we focus on the feasibility of using a specific class of host factors, those involved in innate immune modulation, as broad-spectrum antiviral therapeutic strategies. Finally, a brief summary of major roadblocks derived from targeting host cellular proteins and putative future strategies to overcome its major limitations is proposed.